Dziewictwo Maryi w zrodzeniu Chrystusa na podstawie kazań św. Augustyna na Boże Narodzenie = Virginity of Mary in the Birth of Christ Based on the Christmas Sermons of St Augustine - Jaśkiewicz, Sylwester (2024)
In the context of contemporary culture and mentality, Mary’s virginity in giving birth to Christ might seem a completely archaic and even absurd issue. The only way to overcome this obstacle could involve providing believers with more convincing explanations and substantive and source-based justifications. Against this background, referring to the authority of St. Augustine and his Christmas sermons (In Natali Domini), is not accidental. The article attempts, first of all, to show the birth from the Virgin (Virginis partus) and its message coming from the Christmas teaching of the Bishop of Hippo, which is also the basis of his Mariology. Augustine sees the issue of Mary’s virginity during childbirth (in partu) as a constitutive element of her lasting virginity, which is how it should be understood today.
Dziewictwo Maryi w zrodzeniu Chrystusa jest we współczesnej kulturze i mentalności czymś zgoła archaicznym, a nawet śmiesznym. Stawienie czoła takiej sytuacji wydaje się być możliwe jedynie dzięki dostarczeniu wierzącym bardziej przekonujących wyjaśnień i uzasadnień o charakterze merytorycznym i źródłowym. Odniesienie się w takiej sytuacji do autorytetu św. Augustyna i jego kazań na Boże Narodzenie (In Natali Domini), nie jest przypadkowe. Artykuł stara się w pierwszej kolejności ukazać poród Dziewicy (Virginis partus) i jego przesłanie płynące z bożonarodzeniowego nauczania bi-skupa Hippony, które stanowi zarazem zręby jego mariologii. Augustyn kwestię dziewictwa Maryi w cza-sie porodu (in partu) widzi jako konstytutywny element Jej trwałego dziewictwa i tak też winno ono być odczytywane również dzisiaj.
Keywords: Christmas sermons; Mariology; Mary; St. Augustine; Virgin Birth; Virginity of Mary; Maryja; mariologia; dziewictwo Maryi; poród Dziewicy; św. Augustyn; kazania bożo-narodzeniowe